Pengaruh Pendidikan Kesehatan Tentang Manfaat Daun Torbangun (Coleus Amboinicus L ) Terhadap Pengetahan Ibu Hamil TM III di Yogyakarta - Rahmawati Sholihah, Nur; Yulinda, Dwi; Kumorojati, Ratih; Puspitasari, Dian (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
Exclusive breastfeeding for six months is one of the global strategies to improve infant growth, development, health and survival. Globally, only 38% of babies worldwide are exclusively breastfed. The prevalence of infectious diseases was higher in infants who were not breastfed compared to infants who were breastfed for 0-6 months of life.The factor causing the decline in breastfeeding is the lack of knowledge of breastfeeding mothers about the potential of Indonesian traditional plants that have lactating hormone levels that can be used to increase milk production. A number of foodstuffs in Indonesia that have a function as a laktagogum.The purpose of this study was to determine the effect of health education on the benefits of Torbangun (Coleus Amboinicus L) leaves on the knowledge of pregnant women TM III at the Amanda Pratama Clinic. The type of research used in this study was a pre-experiment with an experimental design of one group pre-post test. The research will be carried out at the Amanda Primary Clinic and will be carried out for 1 month. The population in this study was pregnant women TM III with a sample size of 82. The sampling technique used was simple random sampling. Univatiate analysis with frequency distribution, Bivariate analysis using Marginal Homogenity test and Mc Nemar test. The results of the study, on knowledge (pretest and posttest) obtained the results that the p value <0.05 means that there is a significant effect of health education on knowledge about the benefits of torbangun leaves (Coleus Amboinicus L).